CHALCONE DERIVATIVES AS NRF2 ACTIVATORS - BISWAL, SHYAM; KUMAR, VINEET; JUNG-HYUN, KIM; THIMMULAPPA, RAJESH; MALHOTRA, SANJAY, V; KUMAR, SARVESH (2015)
Compounds and methods for treating or preventing a disease, disorder or condition associated with an Nrf2-regulated pathway, including those associated with an autoimmune disease, comorbidity associated with diabetes, such as retinopathy and nephropathy, bone marrow transplant for leukemia and related cancers, bone marrow deficiencies, inborn errors of metabolism, and other immune disorders, oxidative stress, respiratory infection, ischemia, neurodegenerative disorders, radiation injury, neutropenia caused by chemotherapy, autoimmunity, and congenital neutropenic disorders, and for restoring a corticosteroid responsiveness, in a subject are provided.